2016
DOI: 10.18632/oncotarget.9726
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic translation initiation factor 3B accelerates the progression of esophageal squamous cell carcinoma by activating β-catenin signaling pathway

Abstract: IntroductionEsophageal squamous cell carcinoma (ESCC) is one of the most aggressive malignant tumors. Eukaryotic translation initiation factors 3B (EIF3B) is considered to influence tumor proliferation, invasion, apoptosis and cell cycle, which act together to promote the progression of tumors. However, the role of EIF3B in ESCC is unknown. This study aims to explore the clinical and biological role of EIF3B in ESCC.ResultsEIF3B expressions were up-regulated in both ESCC tissues and cell lines. Overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 24 publications
2
46
0
Order By: Relevance
“…In addition, apoptosis increased after eIF3b depletion. Similar pro-apoptotic effects have been reported in colon cancer 13 , glioblastoma 12 , and esophageal squamous carcinoma 19 . Interestingly, ER-stress-induced apoptosis seemed to be downregulated after eIF3b depletion.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, apoptosis increased after eIF3b depletion. Similar pro-apoptotic effects have been reported in colon cancer 13 , glioblastoma 12 , and esophageal squamous carcinoma 19 . Interestingly, ER-stress-induced apoptosis seemed to be downregulated after eIF3b depletion.…”
Section: Discussionsupporting
confidence: 81%
“…We then showed that eIF3b depletion inhibited cell proliferation by compromising the cell cycle and inducing cell apoptosis. The G1/S arrest after eIF3b depletion has also been noted in bladder cancer 20 , glioblastoma 12 , and esophageal squamous carcinoma 19 . Wang et al found that reduction in overall protein synthesis by eIF3b depletion lead to the smaller size of cells which cannot pass the major size regulatory “R or restriction point” checkpoint, which is also a G1/S arrest reason 20 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…8 Another study investigating the role of eIF3b in esophageal squamous cell carcinoma (ESCC) also revealed that eIF3b expression is much higher in ESCC tissues and ESCC cell lines, while a reduction in eIF3b suppresses cell proliferation and stimulates cell apoptosis through the regulation of the β-catenin signaling pathway. 18 In bladder and prostate cancer cells, eIF3b deletion decreases cell growth and represses the G1/S cell cycle transition by regulating cyclin A, E, Rb, and p27Kip1 protein expression -but not mRNA expression -and it reduces migration as well as interrupting the actin cytoskeleton and focal adhesions. 11 A recently published study showed that knockdown of eIF3b decreases cell viability and promotes apoptosis in osteosarcoma cells due to the regulation of tumor necrosis factor receptor superfamily member 21 (TNFRSF21).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, some studies have revealed that translation initiation factor 3b ( EIF3B ), a key subunit of the largest translation initiation factor that acts to ensure the accuracy of translation initiation, is closely related to oncogenesis [68]. Xu et al [69] reported that EIF3B can accelerate the progression of esophageal squamous cell carcinoma by activating β-catenin signaling, which can promote immune escape and resistance to anti-PD-1 therapy [4]. Thus, copy-number gain of EIF3B may be associated with resistance to anti-PD-1 therapy in melanoma thrugh β-catenin activation.…”
Section: Resultsmentioning
confidence: 99%